(untitled) (The Macau Ricci Institute Journal, 2020)
We are living not only in an epoch of change but in a change of epoch. Forty years ago Ignacio Ellacuría, who was assassinated on the 16th of November 1989 for his commitment for justice and peace in El Salvador, had a prophetic presentiment of this change. He analysed with clarity the crisis in the present global system, which he characterised as a civilization of capital wealth. With great creativity he put forward another model, which he called a civilization of poverty. Pope Francis, from the very beginning of his pontificate, has shown his deep concern for the future of our planet and for a more just global order. In his encyclical Laudato Sí (2015) he insists on the intrinsic connection between the social and ecological challenges that face the world: he invites us to listen both to the cry of the poor and to the cry of the earth. He calls for “a real cultural revolution” directed towards “an integral ecology”. Ellacuría developed the concept of a civilization of poverty in various articles. By “civilization” he meant a global order of human cohabitation. He gives various meanings to the term “poverty”, as did the Latin American bishops at their meeting in Medellín (1968) and the theology of liberation. Fundamentally, it has three meanings. The first takes poverty in a negative sense as the absence or privation of whatis needed to live with dignity: this misery-poverty has to be eradicated. In a second sense, poverty is something positive: the spiritual openness to God and an evangelical counsel of perfection. The third meaning is also positive: it is poverty that gives solidarity with the poor and is a share in the struggle for justice.